Recovery of valuable material from oil palm empty fruit bunch spikelets using sub-critical water treatment - Ahmad Kurnin, Nor Azrin (2018)
Oil palm empty fruit bunch (EFB) was one of the wastes produced in the palm oil mill. Whilst it still contains oil and can even be converted into valuable material, approximately 22.6 million tons is generated annually and treated as solid waste. Current method used by the industries in order to reduce and remove the EFB was by incineration process while some even dispose the EFB in the landfill. This process was known as mulching where the EFB was let to decompose naturally. Both methods were obviously wasting the advantage of fiber in the EFB. Thus, EFB were chosen to undergo sub-critical water (sub-cw) treatment to investigate its conversion into value added products as well as to evaluate the effects of process conditions (reaction temperature and time) of sub-cw treatment on value added products and sugar yield. Sub-cw is defined as water that lies between its boiling point, 100°C and its critical temperature, 374°C. At this condition, several physic-chemical properties of water have been enhanced. For instance, water has very low dielectric constant and higher ion product constant at high temperature (ex: 250°C). Therefore, sub-cw treatment was able to extract non-polar compound like oil and break the lignocelullosic component especially hemicellulose and cellulose into sugar, organic acid, tar and other derivatives. Highest yield of total sugar, 0.382 g/g-dry EFB was obtained at 220°C and reaction time of 5 minutes. Further analysis of the sample by using High Performance Liquid Chromatography (HPLC) detected pentoses and hexoses with yield of 0.008 to 0.032 g/g-dry EFB. Simple sugars which present in the sample at almost all reaction temperature were xylose, glucose, fructose and arabinose. Meanwhile, organic acids found were acetic and lactic acid in which lactic acid was most present in all reaction temperature compared to acetic acid. Highest yield of summation organic acid, 0.189 g/g-dry EFB was obtained at 330°C and reaction time of 5 minutes. Besides, tar was also produced from the reaction, yielded between 0.039 to 0.337 g/g-dry EFB. Phenolic compound were also detected in the tar produced. Highest yield of total phenolic content (TPC) obtained after the treatment was 89.51 mg/g-dry EFB at 330°C. Analysis of tar using Gas Chromatography Mass Spectrometer (GC-MS) indicate that Syringol (2,6-dimethoxy phenol), Guaiacol (2-methoxy phenol), and 4-Ethylguaiacol (4-ethyl, 2-methoxy phenol) were most present in samples at all reaction temperatures. This study showed that many valuable material can be recovered using water at sub-critical condition, and most attractive without the use of harmful organic solvent.